The Effect of Enterprise Risk Management on Financial Performance and Firm Value: The Role of Environmental, Social and Governance Performance - Karina, Ria; Lestari, Factrisia; Ivone, Ivone (Global Financial Accounting Journal, 2023)
Enterprise Risk Management has a crucial role in achieving long-term financial goals and increasing the value of the company. In addition, the focus on environmental, social and governance (ESG) performance is also increasing in business practices and investment decisions. The purpose of this research is to analyze the relationship between corporate risk management with financial performance and corporate value. In addition, this research also aims to determine the role of ESG performance in this relationship. Financial Data is taken from the company's public report listed on the IDX for the period 2017-2021a using purposive sampling method, while ESG performance information is collected from sustainability reports and available ESG data. Panel regression analysis is used to examine the relationship between corporate risk management, financial performance and corporate value. The results showed that ERM significantly positive effect on financial performance and no significant effect on the value of the company. This research also found that the effect of Enterprise Risk Management on financial performance moderated by ESG has a significant negative effect and the effect of Enterprise Risk Management on firm value moderated by ESG has no significant effect.Previous research has not conducted an empirical investigation into how ESG moderation affects how ERM affects a company's performance and values. These findings have significant ramifications for businesses, as they indicate that in order to gain a competitive edge, they must examine the numerous risks and opportunities related to ESG.